Acute Abdomen Cases Presenting At Fauji Foundation Hospital, Rawalpindi (Medical Forum Monthly, 2024)
Study Design: Descriptive study. Place and Duration of Study: This Study was conducted at the Department of Surgery, Fauji Foundation Hospital, Rawalpindi from December 13, 2009 to February 22, 2011. Patients & Methods: A total of 840 patients who presented with acute abdominal pain and were admitted from the emergency department of Fauji Foundation Hospital, Rawalpindi from December, 2009 to February, 2011 were included in the study. The data of the 840 male and female patients was collected on the Patient Performa and then transferred to the data sheet IV of SPSS 10. The results were analyzed by calculating the frequencies of acute abdomen causes. Results: The most frequent cause was non specific abdominal pain (38.7%) followed by acute cholecystitis (7.7%) and acute appendicitis (6.8%). Total exploratory laparotomies done were 204 (24.3%) while 498 (59.3%) patients were managed conservatively with ultrasound abdomen and pain medication. Conclusions: Non specific pain was found to be the most common cause of acute abdomen followed by acute cholecystitis and acute appendicitis. The diagnostic accuracy can be enhanced especially in females of child bearing age by the use of ultrasonography and selective diagnostic laparoscopy.